“Simul iustus et peccator”: Prospettiva ecumenica - Barrajón, L.C., Pedro (Alpha Omega, 2017)
Summary: One of the most controversial issues between Lutheran and Catholic Theologians is the state of the justified with regard to God. For Luther and Reformation theology, man remains a sinner after justification, but the favor manifested in the grace of God given in Christ “covers over” this internal corruption that man has as a consequence of original sin. The formula “simul iustus et peccator” succinctly summarizes this doctrine. Ecumenical dialogue between Lutherans and Catholics after the Joint Declaration on Justification provides new perspectives for achieving a shared understanding of the topic. This article presents this theological issue that is central to a theological understanding of human person in the light of the salvation in Christ. Key words: Luther, Concupiscence, Sin, simul iustus et peccator, Theological Anthropology, Ecumenism. Parole chiave: Lutero, concupiscenza, peccato, simul iustus et peccator, ecumenismo, antropologia teologica.